Differences in lipid profile between acute ischemic and hemorrhagic stroke patients admitted in a referral neuroscience hospital in Dhaka (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Background: Blood lipid levels differently impact ischemic stroke and hemorrhagic stroke. The effect of acute illness on lipid metabolism may alter lipid levels after acute stroke.Objectives: To measure the fasting lipid profile after acute stroke and to compare between ischemic and hemorrhagic stroke.Methods: This cross-sectional study enrolled 247 acute stroke patients (112 hemorrhagic and 135 ischemic; age 59.7 (±13.4) years, 48.6% female) from a referral neuroscience hospital in Dhaka, during February-June 2021. Fasting lipid profile was measured by enzymatic [total cholesterol (TC)], accelerator selective detergent [both high-density lipoprotein cholesterol (HDL-c) and low-density lipoprotein cholesterol (LDL-c)], and glycerol phosphate oxidase method [triglyceride (TG)] by the Abbott Alinity system. Elevated TC, TG and LDL-c were defined as ≥200 mg/dL, ≥150 mg/dL and ≥130 mg/dL respectively while low HDL-c as